The Role of Religious Education in Overcoming Moral and Social Crises among Adolescents - Yusup, Aldian (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Religious education has a very important role in shaping moral and social values in adolescents, especially in the face of increasingly complex moral and social crises. The phenomenon of moral crisis among adolescents, such as violent behavior, drug abuse, and declining social values, shows the importance of efforts to restore morality through religious education. The purpose of this study is to analyze the role of religious education in overcoming moral and social crises among adolescents. This study uses a qualitative method with a literature study approach, which collects data from various articles, books, and journals related to religious education and social behavior of adolescents. The data analysis method used is content analysis by identifying relevant patterns and themes in the literature studied. The results of the analysis show that religious education has a positive impact on shaping adolescents' morality, reducing deviant behavior, and strengthening social values such as empathy, tolerance, and responsibility. In addition, religious education also plays a role in preventing violence and delinquent behavior through teaching the values of peace and conflict resolution. These findings underscore the importance of integrating religious education in the educational curriculum to equip adolescents with a solid moral foundation. However, the effectiveness of religious education in overcoming social crises is also influenced by the cultural context and the quality of teaching received by students.